If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -3x = 8x + 19 Reorder the terms: 49 + -3x = 19 + 8x Solving 49 + -3x = 19 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 49 + -3x + -8x = 19 + 8x + -8x Combine like terms: -3x + -8x = -11x 49 + -11x = 19 + 8x + -8x Combine like terms: 8x + -8x = 0 49 + -11x = 19 + 0 49 + -11x = 19 Add '-49' to each side of the equation. 49 + -49 + -11x = 19 + -49 Combine like terms: 49 + -49 = 0 0 + -11x = 19 + -49 -11x = 19 + -49 Combine like terms: 19 + -49 = -30 -11x = -30 Divide each side by '-11'. x = 2.727272727 Simplifying x = 2.727272727
| 2x+3y-5z=1 | | 6x-5=8+5x | | 5x+4=4x+4 | | X+7=34 | | 2x+10=4x-4 | | 408=10x+22 | | 3(y+6)-y=2(y-9) | | 2(5-x)=4x | | (2x+5)(4x-2)=(2x)(4x) | | (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 | | 5x^2-6x+4=0 | | 3a+8=20 | | 2a+9=17 | | a+1=4 | | X(3)=12 | | 16x-8y=64 | | 4(3q+7)=7 | | 7x+38=-4 | | 11(16-g)=22 | | f=-2f-9 | | -84-8x=9x+18 | | 156-7x=29x+24 |